Shaping Traditional and Modern Approaches to Mitigate Impacts of Mining Industry: A Case Study of Karen Village, Lower Klity Creek, Thailand - Assavarak, Passanan; Arunotai, Narumon; Wiwattanadate, Dawan (Mediterranean Journal of Social Sciences, 2012)
Shaping Traditional and Modern Approaches to Mitigate Impacts of Mining Industry: A case study of Karen Village, LowerKlity Creek, Thailand aims to analyze the effectiveness of mitigation measures, in the past and at present, for solving the problems ofcontamination of lead in waste water releasing from mines into the creek. Secondly, this project also aims to present mitigate measurethat is the hybrid of traditional folk wisdom and modern technology in solving the problem. The study is carried out under documentaryresearch, interview approach and participant observation. The descriptive analysis is designed to analyze the data. As the villagershave to rely on the creek not only as their main food source but also in other consumer activities, they are poisoned by leadcontamination in the creek. This resulted in both physical and mental illness, especially in children; some children died from suchcontamination, while some became disabled. As for the environmental aspect, the ecosystem is severely damaged. This impact resultedin mitigation measures from various sectors to tackle the issue. However, these mitigation measures were not successful due to lack ofconsistency in operations and follow-up, lack of long-term relief budget plan, failure to understand the villagers’ ways of life, and lack ofintegration and extension of further knowledge and practice. Thus, the measure presented in this research is that of a hybrid betweenthe folkways and modern technology in order that the villagers and responsible organizations will be able to adapt it to achieve theeffective solution of the problem in the future.